Proceedings of the International Conference "Aviamechanical Engineering and Transport" (AVENT 2018) 2018
DOI: 10.2991/avent-18.2018.63
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of danger level of pedestrian crossings

Abstract: The present article is devoted to description of some major factors influencing the danger of a pedestrian crossings zone. The review of the factors affecting the number of «vehicles-pedestrians» conflicts in the pedestrian crossing zone was performed. An example of the developed program for determining the danger level of pedestrian crossings on the main streets was given. Keywords-a pedestrian crossing; danger level; width of a pedestrian crossing; road signs; a program for calculation of the danger level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The intersection safety evaluation method based on traffic conflict technology can reflect the operation status of the actual traffic flow effectively and combined with the status of the operation of the intersection evaluation can be a good way to prevent the occurrence of traffic accidents. After summarizing the relevant research [7][8][9][10][11][12][13][14][15][16][17][18], it is found that the following four aspects can be further studied:…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The intersection safety evaluation method based on traffic conflict technology can reflect the operation status of the actual traffic flow effectively and combined with the status of the operation of the intersection evaluation can be a good way to prevent the occurrence of traffic accidents. After summarizing the relevant research [7][8][9][10][11][12][13][14][15][16][17][18], it is found that the following four aspects can be further studied:…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the one hand, there are studies on the analysis and evaluation of various factors affecting the safety of participants at intersections, that quantify the severity of conflicts at intersections. For example, Porkhacheva, S. M [ 7 ] analyzed important factors affecting pedestrian crossing safety at the intersection, studied these factors, and proposed a method to evaluate the degree of danger of crosswalks at the intersection. Kumar, A et al [ 8 ] determined the severity of conflict according to the demographics of pedestrians and their street-crossing behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation